AB0377 Switching from bio-original etanercept to biosimilar etanercept sb4: patient acceptability and outcomes in the real world. (15th June 2017) - Holroyd, C; Wallis, D; Bennett, S; Clayton, P; Edwards, CJ
Abstract : Background: A number of studies have demonstrated the efficacy of biosimilar therapies including SB4 (a biosimilar-etanercept). However, real world data of the process of switching, acceptability to patients, efficacy and safety is lacking. Objectives: To obtain real world data of the acceptability and outcomes of patients with severe (eligible for TNFi therapy as defined by UK NICE) rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) who switch from bio-original etanercept (boDMARD-ETN) to the bsDMARD etanercept SB4 (bsDMARD-ETN). Methods: Adult patients, with RA, PsA & AS, currently enrolled in the SMaRT study and switching from boDMARD-ETN to bsDMARD-ETN were followed for 6 months. Primary outcome was change in DAS28, PsARC response or BASDAI following switching. Additional outcomes included; % change of remission rate, HAQ-DI, CRP or ESR levels, patient satisfaction, PDUS and SAEs leading to discontinuation. All patients had severe disease and were receiving boDMARD-ETN as per local guidelines of UK NICE. Analysis was performed in a similar way to a cross-over RCT trial design where patients act as their own control with the experience in the 6 and 12 months prior to switching used as the control for experience after switching. Patient education and support during the switch included: rheumatologist face to face discussion, letter giving details of the switch and bsDMARD-ETN information sheet, patients invited to discuss switch in clinic, helpline number with patients advised to call for further information or to report adverse events (AEs), routine review in clinic 3 months after switching, and then 6 monthly thereafter or more often if clinically necessary. Results: Following the education and support programme 99% of patients agreed to switch to bsDMARD-ETN (one declined due to concerns about allergic reactions to previous therapies). To date 92 patients have switched from boDMARD-ETN to bsDMARD-ETN and been followed up for more than 6 months (58 RA, 15, AS, 16 PSA and 4 enteropathic arthritis; mean age 55.9 (14.9) yrs, (56 female, 36 male), mean disease duration 16.8 (10.9) yrs, duration on boDMARD-ETN before switch mean 4.85 (3.92) yrs and duration since switch 204.1 (51.4) days. After 6 months following the switch 91% of patients using bsDMARD-ETN have continued with mean last DAS28 – 2.67 (1.32) for RA patients and mean last BASDAI – 4.58 (2.47). Following the switch 8 patients stopped bsDMARD-ETN after mean of 93.6 (56.4) days, the reasons for this were 7/8 clinician/patient determined inefficacy (6 returned to boDMARD-ETN, 1 switched to certolizumab), 1/8 switched after reporting palpitations and poor concentration. In the control period 6 months before switching 17/110 patients stopped boDMARD-ETN (85% continued) including 7 due to primary failure, 7 due to secondary failure, 1 adverse event (AE), 1 patient choice, 1 death (Lung cancer in male ex-smoker with longstanding RA who had received boDMARD-ETN for 10 yrs). Conclusions: An education programme prior to switching to a biosimilar TNFi leads to a high uptake by patients. In follow-up of 6 months after switching from boDMARD-ETN to a bsDMARD-ETN there appears to be a low rate of discontinuation due to inefficacy or AEs. Acknowledgements: Biogen supported this work through an unrestricted grant. Disclosure of Interest: C. Holroyd Speakers bureau: Abbvie, UCB, Roche, Pfizer, D. Wallis: None declared, S. Bennett: None declared, P. Clayton: None declared, C. Edwards Grant/research support from: Abbvie, Roche, Pfizer, Biogen, Speakers bureau: Merk, Abbvie, UCB, Roche, Pfizer, Celgene, Janssen, Celltrion, Lilly